2015
DOI: 10.1016/j.spa.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Optimal online selection of a monotone subsequence: a central limit theorem

Abstract: Abstract. Consider a sequence of n independent random variables with a common continuous distribution F , and consider the task of choosing an increasing subsequence where the observations are revealed sequentially and where an observation must be accepted or rejected when it is first revealed. There is a unique selection policy π * n that is optimal in the sense that it maximizes the expected value of Ln(π * n ), the number of selected observations. We investigate the distribution of Ln(π * n ); in particular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…After a careful analysis, Bruss and Delbaen proved that the mean‐optimal number of monotone increasing selections with Poisson‐many observations is asymptotically normal after centering around false(2nfalse)1/2 and scaling by 31/2false(2nfalse)1/4. Arlotto et al showed that the same asymptotic limit also holds for the discrete‐time problem with n observations so, in summary, we now know that 31/2{Ln(πn)false(2nfalse)1/2}false(2nfalse)1/4N(0,1), as n. …”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…After a careful analysis, Bruss and Delbaen proved that the mean‐optimal number of monotone increasing selections with Poisson‐many observations is asymptotically normal after centering around false(2nfalse)1/2 and scaling by 31/2false(2nfalse)1/4. Arlotto et al showed that the same asymptotic limit also holds for the discrete‐time problem with n observations so, in summary, we now know that 31/2{Ln(πn)false(2nfalse)1/2}false(2nfalse)1/4N(0,1), as n. …”
Section: Introductionmentioning
confidence: 73%
“…, n-the sequential nature of the two selection processes makes the result of Bruss and Delbaen [5] not immediately applicable. The connection between the continuous-time formulation of Bruss and Delbaen [5] and the discrete-time optimization (2) was then argued by Arlotto et al [2] who used the concavity of the map n → E[L n (π * n )] and the O(log n)-bound of Bruss and Delbaen [5] to ultimately confirm the lower bound in (4).…”
Section: Samuels and Steelementioning
confidence: 99%
See 2 more Smart Citations
“…In Sections 5 and 6, we develop the relationship between Theorems 1 and 2 and the more traditional size-focused online selection problem which was first studied in Samuels and Steele [15] and then studied much more extensively by Bruss and Robertson [9], Gnedin [11], Bruss and Delbaen [7,8], and Arlotto et al [3]. On an intuitive level, the time-focused selection problem and the size-focused selection problems are dual to each other, and it is curious to consider the extent to which rigorous relationships that can be developed between the two.…”
mentioning
confidence: 99%